Fabrication and spectroscopic studies on highly luminescent CdSe/CdS nanorod polymer composites - Jana Bomm; Andreas Büchtemann; Angela Fiore; Liberato Manna; James H. Nelson; Diana Hill; Wilfried G. J. H. M. van Sark (Beilstein Journal of Nanotechnology, 2010)
Highly luminescent nanocomposites were prepared by incorporating CdSe/CdS core/shell nanorods into different polymer matrices. The resulting nanocomposites show high transparency of up to 93%. A photoluminescence quantum efficiency of 70% was obtained, with an optimum combination of nanorod (0.05 wt %) and at a UV-initiator concentration of 0.1 wt % for poly(lauryl methacrylate). Nanorods tend to agglomerate in cellulose triacetate.